Particle-in-cell simulation feasibility test for analysis of non-collective Thomson scattering as a diagnostic method in ITER - F. Moradi Zamenjani; M. Ali Asgarian; M. Mostajaboddavati; C. Rasouli (Nuclear Engineering and Technology, 2020)
The feasibility of the particle-in-cell (PIC) method is assessed to simulate the non-collective phenomena like non-collective Thomson scattering (TS). The non-collective TS in the laser-plasma interaction, which is related to the single-particle behavior, is simulated through a 2D relativistic PIC code (XOOPIC). For this simulation, a non-collective TS is emitted from a 50-50 DT plasma with electron density and temperature of ne=3.00×1013cm−3 and Te=1000eV, typical for the edge plasma at ITER measured by ETS system, respectively. The wavelength, intensity, and FWHM of the laser applied in the ETS system are λi,0=1.064×10−4cm, Ii=2.24×1017erg/s⋅cm2, and 12.00ns, respectively. The electron density and temperature predicted by the PIC simulation, obtained from the TS scattered wave, are ne,TS=2.91×1013cm−3 and Te,TS=1089eV, respectively, which are in accordance with the input values of the simulated plasma. The obtained results indicate that the ambiguities rising due to the contradiction between the PIC statistical collective mechanism caused by the super-particle concept and the non-collective nature of TS are resolved. The ability and validity to use PIC method to study the non-collective regimes are verified. Keywords: Particle in cell method, Plasma diagnostics, Non-collective Thomson scattering